Atomic-level localization of π-electrons in defect engineered tri-s-triazine units for increased photocatalytic hydrogen generation of polymeric carbon nitride. Issue 16 (22nd July 2021) - Xue, Mengqi; Jiang, Daochuan; Du, Haiwei; Li, Zhongjun; Bi, Hong; Yuan, Yupeng
Abstract : N defects in tri- s -triazine units can localize π electrons to reduce charge recombination and act as active sites, thus improving the efficiency of photocatalytic hydrogen production. Abstract : Localizing charge carriers close to catalytically active sites can reduce the charge recombination in photoexcited polymeric carbon nitride (PCN), which thus potentially increases its photocatalytic H2 generation. However, this strategy has not been applied to enhance the photocatalytic performance of PCN. Herein density functional theory (DFT) calculations unravel that N defect (Ndefect ) engineered tri- s -triazine units form a highly localized mid-gap state in PCN, which can localize the π electrons for efficient separation of electrons and holes. Moreover, Ndefect engineered tri- s -triazine units impart the lowest Gibbs free energy barrier of −0.129 eV for the reduction of H + to adsorbed H, thereby serving as the catalytically active sites. Enlightened by theoretical results, the Ndefect engineered tri- s -triazine units were created via post oxidation of PCN in an electronic furnace. Such PCN with N defects offers an increased photocatalytic H2 generation under visible light exposure. The highest H2 generation rate is up to 98.1 μmol h −1, 3.8 times higher than that by using pristine PCN (26.1 μmol h −1 ). This work manifests the significance of localizing charge carriers close to the catalytically active sites for increased photocatalytic performance of PCN.